Influence of Stand-off Distance on the Blast-Resistance of Steel Plate Supported Concrete Walls - Yildiz, Rasid Ahmed (International Conference on Applied Engineering and Natural Sciences, 2023)
The influence of stand-off distance for the protective performance and capability of the steel plate supported concrete barriers is modelled, within the current work. Steel and concrete have been used for centuries to build protective structures. Due to the military's concern with mitigating the effects of explosions and bullets, they have both collectively seen major improvements as a material for protective constructions. The significance of stand-off distance on the durability of steel plate supported concrete wall is investigated through simulations. Johnson-Cook hardening and damage molds have been used to define the mechanical behavior of steel, while concrete damage plasticity has been used to define the behavior of concrete. The growth of detonation products is modeled using the JWL equation of state, in which CompB is selected as explosive. Coupled-Eulerian-Lagrangian methodology is employed in the constructed finite element model. The outcomes demonstrated that the stand-off distance has a substantial impact on a structure's durability. The explosives' ability to cause damage is less effective as stand-off distance increases. For the case that the stand-off distance is 50 mm, the explosion completely destroyed both the 10 mm thick steel plate and the concrete. However, according to the simulation's findings at the stand-off distance of 300 mm, the structure has sustained relatively minor damage. Also, the steel plate functioned as a protective barrier in most cases, as designed.